Breastfeeding Self-efficacy of Women With and Without Gestational Diabetes. Issue 3 (May 2016) - Chertok, Ilana R.A.; Sherby, Elissa
Abstract: Purpose: The purpose of the study was to examine the breastfeeding self-efficacy of women with and without gestational diabetes mellitus (GDM). Breastfeeding rates among women with GDM are often lower than rates of women without GDM, possibly related to early breastfeeding challenges that may negatively affect breastfeeding self-efficacy. Study Design and Methods: The breastfeeding self-efficacy scale short form (BSES-SF) survey was used to compare breastfeeding self-efficacy of 32 women with GDM and 35 women without GDM who gave birth to singleton, term (≥37 weeks gestation) baby in an Israeli hospital. Linear regression analysis was used to determine factors associated with BSES-SF scores in the first week postpartum. Results: In the final regression model, significant factors associated with higher BSES-SF scores were no perceived delayed lactogenesis II (beta = -0.24, p = 0.050) and earlier initiation of breastfeeding (beta = -0.31, p = 0.011). Clinical Implications: Factors significantly associated with BSES-SF scores can be addressed through encouragement and support of breastfeeding by healthcare providers. Lactation support in the early postpartum period should focus on facilitation of early and frequent breastfeeding and/or milk expression to decrease risk of delayed breastfeeding initiation and to minimize risk of perceived delayed lactogenesis II. Early lactation support is especially important among women at increased risk for delayed breastfeeding initiation or perceived delayed lactogenesis II such as women with GDM in pregnancy. Abstract : Women with gestational diabetes are at risk for breastfeeding challenges. Initiation of breastfeeding as soon as possible immediately after birth was found to be helpful in promoting successful breastfeeding among this population.